2013
DOI: 10.1074/jbc.m113.503763
|View full text |Cite
|
Sign up to set email alerts
|

Ptc1 Protein Phosphatase 2C Contributes to Glucose Regulation of SNF1/AMP-activated Protein Kinase (AMPK) in Saccharomyces cerevisiae

Abstract: Background: SNF1/AMP-activated protein kinases (AMPKs) are central energy regulators that are inactivated by dephosphorylation of the activation loop. Results: Mutation of Ptc1 protein phosphatase 2C (PP2C) affects dephosphorylation of SNF1/AMPK in Saccharomyces cerevisiae. Conclusion: Ptc1 and Sit4 type 2A-related phosphatase contribute to glucose-regulated dephosphorylation, whereas Reg1-Glc7 PP1 plays the major role. Significance: At least three phosphatases regulate yeast SNF1/AMPK in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…However, inappropriately elevated Snf1 activity may be deleterious to cell growth (13,44). Consistent with this idea, the reg1⌬ ubp8⌬ ubp10⌬ mutant may sense elevated Snf1 activity and then transmit a signal to a Snf1 synthesis mediator to restore Snf1 protein levels (Figs.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, inappropriately elevated Snf1 activity may be deleterious to cell growth (13,44). Consistent with this idea, the reg1⌬ ubp8⌬ ubp10⌬ mutant may sense elevated Snf1 activity and then transmit a signal to a Snf1 synthesis mediator to restore Snf1 protein levels (Figs.…”
Section: Discussionsupporting
confidence: 59%
“…3G). To test the hypothesis that Snf1 protein level can also be altered in response to its phosphorylation status, we deleted REG1 to impair Snf1 dephosphorylation (12,13,43,44). Surprisingly, although deletion of REG1 (encoding a dominant phosphatase of Snf1) did not affect Snf1 phosphorylation in ubp8⌬ ubp10⌬ cells (Fig.…”
Section: Enhanced Phosphorylation Of Snf1 Restores Its Protein Level mentioning
confidence: 99%
“…Subsequent work demonstrated that Ptc1 is required for normal TOR signaling by regulating, in a HOG-independent manner, a step upstream of the Sit4 phosphatase (Gonzalez et al 2009). Recently, Ptc1 has been shown to dephosphorylate the Snf1 protein kinase at Thr 210 in vivo (Ruiz et al 2013).Early work showed that mutations in PTC1 could suppress phenotypes derived from hypoactive pkc1 alleles (Huang and Symington 1995), thus pointing to a link between Ptc1 and the cell-wall integrity (CWI) pathway. This pathway is composed of several membrane sensors that signal through the small GTPase Rho1 to the Pkc1 kinase.…”
mentioning
confidence: 99%
“…Subsequent work demonstrated that Ptc1 is required for normal TOR signaling by regulating, in a HOG-independent manner, a step upstream of the Sit4 phosphatase (Gonzalez et al 2009). Recently, Ptc1 has been shown to dephosphorylate the Snf1 protein kinase at Thr 210 in vivo (Ruiz et al 2013).…”
mentioning
confidence: 99%
“…Budding yeast AMPK activation highlights the importance of phosphatases, as the upstream activating kinases do not appear to be regulated (8,16). Rather, dynamic control may come from protein phosphatases, and PP2C, PP1, and PP6 have been implicated in deactivating budding yeast AMPK (10,17,18).…”
mentioning
confidence: 99%